The European Pentarchy and the Congress of Verona, 1822 - Nichols, I.C. author. aut Link
377 p.
Keywords: For one reason or another. modem historians have neglected the Congress of Verona. some because they thought the field already had been thoroughly plowed. while others doubted that enough material could be found for more than an article or two on the subject. Indeed. not a single book-length monograph of this international assembly has ever been published in any language. This study. therefore. attempts to fill the gap by (1) explaining the genesis of the Congress. (2) furnishing a comprehensive account of its work. (3) revising some of the interpretations of Sir Charles K. Webster. Harold W. V. Tempedey. and others. and (4) analyzing the significance of the Congress. with emphasis on its contribution to the fall of the Quintuple Alliance. a consequence aided by the dissimilar and often contradictory interests of the allies themselves. This book is essentially a diplomatic history. but diplomats. of course. do not live in a vacuum. Numerous political. social. commercial. financial. and sometimes even religious factors. impinge upon their consciousness.